Assessing the Impact of a TOEFL Preparation Program on TOEFL Performance among Lecturers at a University in North Maluku - Ummi Salamah Tianotak; Dwi Budidarma Sutrisno (Jurnal Bahasa Inggris Terapan, 2026)
This study aims to examine the progress achieved by participants in a TOEFL preparation program, as reflected in their TOEFL pre-test and post-test scores. The participants attended 24 TOEFL preparation sessions, and their performance before and after completing the program was compared to evaluate the program's effectiveness. The participants of this study consisted of university lecturers from one of the public universities in Indonesia, coming from different disciplines. This study employed a quantitative experimental design. The data were taken from the pre-test and post-test at the beginning and end of the TOEFL preparation program. The pretest and posttest data were then analyzed using descriptive statistics and a paired sample t-test. The findings reveal that although some participants showed individual score fluctuations across the skills, the overall results did not indicate statistically significant improvement in TOEFL performances. The paired sample t-test showed that the p-value of .537 is greater than the conventional significance level of α=0.05. Therefore, the null hypothesis failed to be rejected. It can be concluded that the TOEFL preparation for lecturers at a university in North Maluku did not result in a statistically significant improvement in their overall TOEFL scores.